MÉTODO DOS ELEMENTOS FINITOS COM INTEGRAÇÃO REDUZIDA NA SIMULAÇÃO DA CONTAMINAÇÃO DE ÁGUAS SUBTERRÂNEAS - Dias, Claudia M.; Garcia, Eduardo L. M.; Loula, Abimael F. D.; Coutinho, Alvaro L. G. (Águas Subterrâneas, 2003)
Indisponível